Bibliometrix Application on Halal Tourism Management Research - Sabiq Al Qital (Journal of Islamic Economics Literatures, 2022)
This research aims to find out and map research related to the development of Halal Tourism Management research trends published by leading journals on Halal Tourism Management policy. The analysis focused on describing the characteristics and trends of the keywords, authors, and journals. The data analyzed were from 191 research publications in Scopus. The search terms were “Halal Tourism Management”. The searches used to establish the study dataset were last updated on May 11, 2022. Descriptive statistical methods were used, and a bibliometric analysis was conducted using Biblioshiny, an R-based app, to generate a bibliometric map. This study has found that the basic themes of this topic are "Travelers Destinations Countries", "Muslim Tourists Destinations", and "Halal Tourism Indonesia". And the destination countries for halal tourism are not only Muslim countries, but there are non-Muslim countries that are developing halal tourism management such as; Japan, North Korea, Australia, and Thailand. The originality offered by this research is the use of the biblioshiny analysis tool by the R program.The limitations of this research include the time for data analysis is not long enough. The findings of this study can provide insight for regulators and academics to develop marketing strategies and management of halal tourism.